Is narrow qrs complex tachyarrythmia always from supraventricular? - Tiya Setiadi; Hauda El Rasyid (Faculty of Medicine, Universitas Andalas, 2020)
Idiopathic left ventricular tachycardia (previously known as fascicular VT) is characterized by right bundle branch block (RBBB) left axis ventricular tachycardia (VT) with a relatively narrow QRS (120–140 ms) in young patients and sensitive to verapamil. Objective: To remind that not all tachyarrhythmias with relatively narrow QRS are derived from supraventricular. Cases: First case of 23 years old man with chief complain palpitation and presyncope with narrow QRS ventricular tachycardia electrocardiography (ECG). Second case of 16 years old man with chief complain palpitation with narrow QRS ventricular tachycardia ECG, both of them are getting better after administration of diltiazem and verapamil. Conclusions: Idiopathic left ventricular tachycardia is associated with presyncope, palpitation and was successfully terminated with verapamil. Medical management is variable in its outcomes and given the age of the population affected. Narrow QRS complex tachycardia not always from supraventricular, we should think about ventricular tachycardia especially ILVT if there is no structural heart disease.